Dual Primary Squamous Cell Carcinoma of the Lung and Adenocarcinoma Rectal - Sayyid Muhammad Sahil Haikal; Hadi Irawiraman; Aryo Dirgantara Putra (Faculty of Medicine Universitas Airlangga, 2023)
Introduction: Lung and colorectal carcinoma are commonly found in cancer and often cause mortality worldwide. Colorectal cancer (CRC) is the third most common cause of death. Although multiple primary cancers can exist, these two malignancies rarely happen simultaneously. This case report shows a patient diagnosed with squamous cell carcinoma of the lung and rectal adenocarcinoma with metastases to the liver, ocular, and cerebrum. Case: A 54-year-old woman came with chest pain accompanied by persistent and progressive breathing difficulty, cough, loss of appetite, and weight loss of almost 15 kg. The patient experienced sudden lower and upper extremities weakness two weeks after being hospitalized. The patient also experienced blurred vision and swelling of the eyes. At that time, the patient had an endoscopy procedure, and the biopsy showed colitis with severe dysplasia. Based on clinical and radiologic findings, the patient had lung and colon cancer. Conclusion: Dual primary carcinoma rarely happens, and metastases from different neoplasms are difficult. Warren and Gates' criteria could be used to diagnose dual primary carcinoma, especially if diagnostic studies could not be performed. Signal that the hedgehog gene is still active when the neonate is born is suspected of causing these carcinomas.